Ultrahigh quality microlasers from controlled self‐assembly of ultrathin colloidal semiconductor quantum wells - Thung, Yi Tian (2023)
Colloidal quantum wells (CQWs) have emerged as a promising class of gain material in various optical feedback configurations. This is due to their unique excitonic features arising from their 1D quantum confinement. However, existing methods for integrating CQW onto microresonators will cause low laser quality due to uneven CQW coating. To overcome this, the use of liquid-interface kinetically driven self-assembly is proposed to coat ultrathin, close-packed layers of colloidal CdSe/Cd1−xZnxS core/shell CQWs between 7 and 14 nm onto the surface of silica microsphere cavities. The fabricated CQW-whispering-gallery-mode microlasers possess a commendable high quality (Q) factor of 13 000 at room temperature. Stable single-mode lasing output is demonstrated through evanescent field coupling between a CQW-coated microsphere and a thin uncoated microfiber in a 2D-3D microcavity configuration. These promising results highlight the suitability of the liquid-interface kinetically driven self-assembly method for realizing ultrathin CQW-coated microlasers and its high compatibility for integrating colloidal nanocrystals onto complex 3D microstructures for future miniaturized colloidal optoelectronic and photonic applications.